Step
*
1
2
of Lemma
es-increasing-sequence
1. es : EO@i'
2. m : ℕ+@i
3. f : ℕm ─→ E@i
4. ∀i:ℕm - 1. (f i <loc f (i + 1))@i
5. ∀d:ℕ. ∀i:ℕm. ∀j:ℕi.  (((i - j) ≤ d) 
⇒ (f j <loc f i))
⊢ ∀i:ℕm. ∀j:ℕi.  (f j <loc f i)
BY
{ (Auto THEN (InstHyp [⌈i - j⌉; ⌈i⌉; ⌈j⌉] (-3))⋅ THEN Auto') }
Latex:
1.  es  :  EO@i'
2.  m  :  \mBbbN{}\msupplus{}@i
3.  f  :  \mBbbN{}m  {}\mrightarrow{}  E@i
4.  \mforall{}i:\mBbbN{}m  -  1.  (f  i  <loc  f  (i  +  1))@i
5.  \mforall{}d:\mBbbN{}.  \mforall{}i:\mBbbN{}m.  \mforall{}j:\mBbbN{}i.    (((i  -  j)  \mleq{}  d)  {}\mRightarrow{}  (f  j  <loc  f  i))
\mvdash{}  \mforall{}i:\mBbbN{}m.  \mforall{}j:\mBbbN{}i.    (f  j  <loc  f  i)
By
(Auto  THEN  (InstHyp  [\mkleeneopen{}i  -  j\mkleeneclose{};  \mkleeneopen{}i\mkleeneclose{};  \mkleeneopen{}j\mkleeneclose{}]  (-3))\mcdot{}  THEN  Auto')
Home
Index